Surface Interactions Studies of Novel Two-Dimensional Molybdenum Disulfide with Gram-Negative and Gram-Positive Bacteria. (22nd January 2023) - Adam, Jaber; Del Sorbo, Maria Rosaria; Kaur, Jasneet; Romano, Rocco; Singh, Manjot; Valadan, Mohammadhassan; Altucci, Carlo
Abstract: The interaction between two-dimensional nanoflakes and bacteria in water-based physiological liquids is a hot topic that unveils new types of phenomena and is fundamental to bioscience applications. In this work, we extend Derjaguin, Landau, Verwey, and Overbeek theory (DLVO theory) that describes the properties of nano-objects in solutions, to the case of two-dimensional nanoflakes interacting with bacteria cell membranes, both for Gram-positive and Gram-negative bacteria. We have studied the role of the bacterial shape, membrane potential, and two-dimensional nanomaterials nature showing the interplay of these parameters in determining whether the interactions are attractive or repulsive and whether electrostatic or van der Waals forces are dominant. We calculated the interaction distances at equilibrium for different bacterial species and hydrophobic nanomaterials such as M o S 2 in two environmentally friendly solvents, water and cyrene.